The Relationship Between Climate Change and the Prevalence of Environmentally Based Diseases in Coastal Fishermen Communities in Sorue Jaya Village, Soropia District - Hariati Lestari; Wa Ode Liska Nur Aurin; Nurmut Maemuna; Sabrina Wahyuni Meyitia; Sakriani; Siti Nurselfina Wati; Uci Ndariani; Dewi Faridah (Journal of Epidemiology and Health Science, 2025)
Background: Climate change exerts significant impacts on coastal communities, particularly fishing populations, who are highly vulnerable to environment-related diseases such as diarrhea, malaria, skin infections, and acute respiratory infections (ARI). Objective: This study aims to analyze the relationship between climate change and the prevalence of environmental-based diseases among coastal fishing communities in Sorue Jaya Village, Soropia District, Konawe Regency. Methods: This quantitative study utilized a cross-sectional design involving 210 respondents. Data were collected using structured questionnaires that explored perceptions of climate change and the occurrence of environmental-based diseases. Statistical analysis was conducted using the Chi-Square test via SPSS version 25.0. Results: The analysis revealed a statistically significant relationship between irregular rainfall patterns and the incidence of diarrhea (p = 0.030). However, other climatic variables such as increased air temperature, strong winds, and high sea waves did not show significant associations with the incidence of diarrhea or other environmental-based diseases. Similarly, no significant relationships were found between climate change and the incidence of dengue fever, malaria, skin diseases, or ARI. Conclusion: Climate change influences the prevalence of certain environmental-based diseases. In Sorue Jaya Village, erratic rainfall was significantly associated with the incidence of diarrhea. However, other climate-related factors such as temperature fluctuations, strong winds, and high sea waves were not significantly related to the prevalence of dengue fever, malaria, skin diseases, or ARI. Despite these findings, environmental changes driven by climate variability remain important determinants of health risk in coastal communities and warrant continued attention in public health planning. Keywords: Climate Change, Diarrhea, Fishing Communities, Disease Incidence, Prevalence